2016
DOI: 10.1111/epi.13337
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of and attitudes toward counseling about SUDEP and other epilepsy risk factors among Austrian, German, and Swiss neurologists and neuropediatricians

Abstract: SUMMARYObjective: To examine the attitudes toward counseling about sudden unexpected death in epilepsy (SUDEP) and other epilepsy risk factors among Austrian, German, and Swiss neurologists and neuropediatricians, and to determine factors associated with not discussing SUDEP. Methods: Questionnaires were sent to approximately 5,000 neurologists and neuropediatricians in 2014 regarding respondents' demographics, their working environments, and how often they discussed SUDEP, suicidal ideations on anticonvulsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 38 publications
2
49
2
1
Order By: Relevance
“…We found a higher mortality rate in this small population of patients with PNES than in controls. Several factors are responsible for the elevated mortality rates found in childhood, adolescent, and adult epilepsy [1,34], including seizure severity, underlying diseases, medication, comorbidities, and life-style factors [35][36][37]. A previous study also reported greater mortality in PNES [38].…”
Section: Discussionmentioning
confidence: 95%
“…We found a higher mortality rate in this small population of patients with PNES than in controls. Several factors are responsible for the elevated mortality rates found in childhood, adolescent, and adult epilepsy [1,34], including seizure severity, underlying diseases, medication, comorbidities, and life-style factors [35][36][37]. A previous study also reported greater mortality in PNES [38].…”
Section: Discussionmentioning
confidence: 95%
“…The same applies to referral to epilepsy surgery that takes a mean epilepsy duration at presurgical assessment of 18 years [48], although referral should be accomplished upon failure of two AED regimens. A recent survey in Austria, Germany and Switzerland on discussing epilepsy-associated risks with patients showed that a high proportion of neurologists and neuropaediatricians discuss restrictions in driving and risks of daily life but defer from discussing SUDEP or suicidal ideation on AEDs with their patients [49]. Possible causes for limitations in guideline implementation include difficulties in leaving older and previously used therapeutic strategies in favour of new guidelines, lack of interest in clinical guidelines, decreased self-efficacy and lack of time [16,50].…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of SUDEP deaths may be explained by a high rate of drugrefractory epilepsy, which is a major risk factor of SUDEP. The risk of SUDEP should be discussed with patients with epilepsy and their caregivers in an appropriate setting [140,141]. Infections such as aspiration pneumonia common in one study [104] can be sequelae of bilateral tonic-clonic seizures.…”
Section: Individual and Caregiver Quality Of Lifementioning
confidence: 99%